An Internet of Things-Based Smart Monitoring System for Soil Moisture and Temperature - Ahmad Sofyan Sulaeman; Vina Umaya Octaviani; Muhamad Agung Suhendra (TIME in Physics, 2026)
The development of Internet of Things (IoT) technology provides significant opportunities for the application of smart farming to improve the effectiveness of monitoring plant environmental conditions. This study aims to design and build an IoT-based soil monitoring system capable of measuring soil moisture and temperature parameters in real-time. The designed system uses a soil moisture sensor, a temperature sensor, an ESP32 microcontroller, an RTC module, and a microSD. Measurement data is displayed via the Blynk application and Telegram notifications so that it can be accessed remotely. The research method is carried out through several stages, namely literature review, site selection and preparation, hardware assembly, system testing, and sensor calibration. Soil moisture and temperature data are collected periodically at certain time intervals and stored for analysis purposes. The results of the 10-hour test show that the system is able to perform well, indicated by fairly stable sensor readability after calibration and the ability to send data to the Blynk and Telegram applications in a timely manner. Based on the research results, this IoT-based soil monitoring system can help users monitor soil environmental conditions efficiently and accurately.